Evaluating the contributions of different organic matter sources to urban river water during a storm event via optical indices and molecular composition. (15th November 2019) - Lee, Mi-Hee; Lee, Yun Kyung; Derrien, Morgane; Choi, Kwangsoon; Shin, Kyung Hoon; Jang, Kyoung-Soon; Hur, Jin
Abstract: Dissolved organic matter (DOM) in river water dynamically changes with respect to its major sources during heavy rain events. However, there has been no established tool to estimate the relative contributions of different organic sources to river water DOM. In this study, the evolution in the contributions of ten different organic matter (OM) sources to storm water DOM was explored with a selected urban river, the Geumho River in South Korea, during storm events via an end-member mixing analysis (EMMA) based on fluorescence indices and Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). The OM source materials included treated effluent, road runoff, groundwater, topsoil, deep soil, leaves, reeds, riparian plants, attached algae, and suspended algae. The EMMA results provided quantitative estimates of the variations in the dominant OM sources with the progress of storms. Treated effluent was the prevailing source at the beginning period of the storm, while topsoil, leaves, riparian plants, and groundwater predominated during and after the peak period. The fluorescence indices-based evaluation was consistent with the statistical comparison of the molecular formulas derived from FT-ICR-MS conducted on the ten potential OM sources and the storm samples. The observed variations in the OM sources agreed with the typical characteristics of urban rivers in connection with anthropogenic inputs and the impact of surrounding impervious surfaces. This study demonstrates the application of intuitive and facile tools in estimating the relative impacts of OM sources in urban watersheds. Graphical abstract: Image 1 Highlights: It is the first study using FT-ICR-MS for OM source tracking during a storm. A quantitative evaluation is firstly performed for dynamic variations in DOM sources. Treated effluent and top soil prevailed before and after peak, respectively. Optical indices-based EMMA results were consistent with FT-ICR-MS data. The EMMA provided a reliable tool for OM source tracking for urban watersheds.